Human-like movement of an anthropomorphic robot: problem revisited - Silva, Eliana Oliveira Costa (2011)
Human-like movement is fundamental for natural human-robot interaction and collaboration. We have developed in a model for generating arm and hand movements an anthropomorphic robot. This model was inspired by the Posture-Based Motion-Planning Model of human reaching and grasping movements. In this paper we present some changes to the model we have proposed in [4] and test and compare different nonlinear constrained optimization techniques for solving the large-scale nonlinear constrained optimization problem that rises from the discretization of our time-continuous model. Furthermore, we test different time discretization steps.